Implementasi Pelayanan Prima (Service Excellence) pada Bank Muamalat KCP Pasuruan untuk Memaksimalkan Kepuasan Nasabah (Studi pada Bank Muamalat KCP Pasuruan) - Nur Illaiyah Mardi (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
Service is one of the important factors that must be owned by a bank, because banking is a business entity engaged in the service sector. Excellence service is important to achieve customer satisfaction. Because service will leave an impression on service users so that they will continue to come back. This is what makes banks have to provide maximum service to satisfy their customers, because if the service provided is not good, then the customer will switch to another bank. To provide maximum excellence service to customers, the bank must prepare personnel who are able to handle the desires and needs of its customers. The personnel who are expected to be able to help the desires and needs of their customers are customer service. The research method used in this study is a qualitative method, namely research that intends to understand the phenomenon of what is experienced by the research subject holistically and by means of description in the form of words and language. The technique used by the researcher is through direct observation and interviews with samples of customer service employees. The results of the study indicate that Bank Muamalat KCP Pasuruan has implemented excellence service standards effectively.